BESFA: bioinformatics based evolutionary, structural & functional analysis of prostate, Placenta, Ovary, Testis, and Embryo (POTE) paralogs - Qazi, Sahar; Jit, Bimal Prasad; Das, Abhishek; Karthikeyan, Muthukumarasamy; Saxena, Amit; Ray, M. D.; Singh, Angel Rajan; Raza, Khalid; Jayaram, B.; Sharma, Ashok (Heliyon, 2022)
The POTE family comprises 14 paralogues and is primarily expressed in Prostate, Placenta, Ovary, Testis, Embryo (POTE), and cancerous cells. The prospective function of the POTE protein family under physiological conditions is less understood. We systematically analyzed their cellular localization and molecular docking analysis to elucidate POTE proteins' structure, function, and Adaptive Divergence. Our results suggest that group three POTE paralogs (POTEE, POTEF, POTEI, POTEJ, and POTEKP (a pseudogene)) exhibits significant variation among other members could be because of their Adaptive Divergence. Furthermore, our molecular docking studies on POTE protein revealed the highest binding affinity with NCI-approved anticancer compounds. Additionally, POTEE, POTEF, POTEI, and POTEJ were subject to an explicit molecular dynamic simulation for 50ns. MM-GBSA and other essential electrostatics were calculated that showcased that only POTEE and POTEF have absolute binding affinities with minimum energy exploitation. Thus, this study's outcomes are expected to drive cancer research to successful utilization of POTE genes family as a new biomarker, which could pave the way for the discovery of new therapies.
Keywords: (MMGBSA); Adaptive divergence; Evolution; generalized born surface area; Homology; Mechanics; Molecular docking; Molecular dynamic simulation molecular; POTE paralogs